Empowering Women through Microfinance: Catalizing Societal Transformation via Entrepreneurship - Nepal, Pramshu (The Lumbini Journal of Business and Economics, 2023)
Microfinance has emerged as a transformative tool addressing financial needs, especially for marginalized communities with a focus on empowering women. This study investigates the impact of microfinance on women’s entrepreneurship and societal transformation via entrepreneurship in Butwal sub-metropolitan city emphasizing decision-making, effectiveness, lifestyle changes, and the reduction of domestic violence and gender inequality. Surveying 100 women entrepreneurs, the study reveals significant positive effects of microfinance. It empowers women in decision-making, enhances effectiveness, uplifts living standards, promotes investments, and reduces domestic violence. Microfinance fosters entrepreneurship, challenges patriarchal norms, and contributes to economic growth and social change. Correlation analysis demonstrate strong associations between women entrepreneurship development and other variables. The findings underscore the vital role of microfinance in women’s empowerment and economic development. Policymakers need to prioritize regulatory support and targeted interventions to sustain and enhance the microfinance sector, ensuring inclusive economic growth and empowerment of women entrepreneurs.